1999
DOI: 10.1007/s004970050166
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of self-incompatibility in a natural population of Petunia axillaris (Solanaceae) in Uruguay containing both self-incompatible and self-compatible plants

Abstract: Many members of the Solanaceae display a type of gametophytic self-incompatibility which is controlled by a single multiallelic locus, called the S-locus. From our previous survey of more than 100 natural populations of Petunia axillaris (a solanaceous species) in Uruguay, we had found that the majority of the populations of subspecies axillaris were comprised of virtually all self-incompatible individuals. The rest were "mixed populations" which contained mostly self-incompatible and some self-compatible indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 32 publications
1
55
0
5
Order By: Relevance
“…Alternatively, this plant may be homozygous and possibly self-compatible. This does not necessarily indicate a breakdown of GSI in the L. parishii population, as a low frequency of SC individuals has been reported for other populations with GSI (eg, Tsukamoto et al, 1999;Stone and Pierce, 2005).…”
Section: Ae Savage and Js Millermentioning
confidence: 75%
“…Alternatively, this plant may be homozygous and possibly self-compatible. This does not necessarily indicate a breakdown of GSI in the L. parishii population, as a low frequency of SC individuals has been reported for other populations with GSI (eg, Tsukamoto et al, 1999;Stone and Pierce, 2005).…”
Section: Ae Savage and Js Millermentioning
confidence: 75%
“…In Campanula rapunculoides, analyses of 31 parental families suggested the presence of 3-5 unlinked, mostly recessive genetic modifiers affecting the strength of the SI response (GoodAvila and Stephenson 2002). In P. axillaris, the presence of self-compatible plants has been shown to be due to three different mechanisms: a linked gene that suppresses the expression of a specific S-RNase gene (Tsukamoto et al 2003a), a loss of function on the pollen component of SI (Tsukamoto et al 2003b), and the presence of unlinked modifiers (Tsukamoto et al 1999). The variable strength of SI has been shown in most cases in species with small patchy populations such as weeds (Baker 1965), island colonizers (Bateman 1952;Burd 1994), and populations growing in peripheral habitats (Busch 2005); these populations typically undergo repeated events of colonization and local extinction and usually consist of a small number of individuals and are likely to experience reduced pollinator and mate availability.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also shown that duplication of the S-locus can lead to breakdown of the GSI response (De Nettancourt 1977Stone 2002), specifically the duplication of the pollen-expressed component of the GSI reaction of the Solanaceae (Tsukamoto et al 1999). Our findings, however, are unlikely to be the result of a duplicated pollen determinant of SI because if the pollen component of the S-locus, S-locus F-box protein (Sijacic et al 2004), is duplicated, then an allele carrying such duplication will be rendered fully selfcompatible (Kao and Tsukamoto 2004) and such mutations are not likely to vary the strength of the SI response with floral age or prior fruit development (Good-Avila and Stephenson 2002) as we observed in our previous studies (Stephenson et al 2003;Travers et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although S-RNase and SLF/SFB define pollen rejection S-specificity, modifier genes unlinked to the S-locus are required for self-incompatibility (SI; Martin, 1968;Ai et al, 1991;Murfett et al, 1996;Tsukamoto et al, 1999).…”
mentioning
confidence: 99%